2016
DOI: 10.18632/oncotarget.7313
|View full text |Cite
|
Sign up to set email alerts
|

G protein-coupled receptor GPR160 is associated with apoptosis and cell cycle arrest of prostate cancer cells

Abstract: G protein-coupled receptors (GPCRs) represent the largest membrane protein family implicated in the therapeutic intervention of a variety of diseases including cancer. Exploration of biological actions of orphan GPCRs may lead to the identification of new targets for drug discovery. This study investigates potential roles of GPR160, an orphan GPCR, in the pathogenesis of prostate cancer. The transcription levels of GPR160 in the prostate cancer tissue samples and cell lines, such as PC-3, LNCaP, DU145 and 22Rv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 35 publications
0
24
0
Order By: Relevance
“…Among the GPCRs, orphan GPCRs have high potential as therapeutic targets . Some orphan GPCRs, such as GPRC6A and GPR160, are involved in prostate cancer cell proliferation and disease progression . However, the significance of other orphan GPCRs in prostate cancer is elusive.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the GPCRs, orphan GPCRs have high potential as therapeutic targets . Some orphan GPCRs, such as GPRC6A and GPR160, are involved in prostate cancer cell proliferation and disease progression . However, the significance of other orphan GPCRs in prostate cancer is elusive.…”
Section: Introductionmentioning
confidence: 99%
“…11 Some orphan GPCRs, such as GPRC6A and GPR160, are involved in prostate cancer cell proliferation and disease progression. 12,13 However, the significance of other orphan GPCRs in prostate cancer is elusive. In our study, we sought to identify orphan GPCRs that could serve as novel therapeutic target molecules for progressive prostate cancer.…”
Section: Introductionmentioning
confidence: 99%
“…These GPCRs, which are normally expressed in fully differentiated, post-mitotic neuronal cells, are able to induce cellular oncogenic transformation when introduced to an ectopic environment of proliferating cells and activated by agonist 7,8 . In addition to oncogenes and tumorsuppressor genes essential for cancer initiation and progression, autocrine and/or paracrine secretion of GPCR-activating molecules and their downstream signaling events affect tumor growth, survival, and metastasis 1,[9][10][11][12][13][14] .…”
Section: Highlightsmentioning
confidence: 99%
“…These GPCRs, which are normally expressed in fully differentiated, post-mitotic neuronal cells, are able to induce cellular oncogenic transformation when introduced to an ectopic environment of proliferating cells and activated by agonist 7,8 . In addition to oncogenes and tumorsuppressor genes essential for cancer initiation and progression, autocrine and/or paracrine secretion of GPCR-activating molecules and their downstream signaling events affect tumor growth, survival, and metastasis 1,[9][10][11][12][13][14] .Olfactory receptors (ORs) are the largest family of GPCRs present in the olfactory epithelium but are also found in various ectopic or non-olfactory locations such as prostate, heart, placenta, embryo, erythroid cells, spleen, kidney, gut, tongue, and carotid body [15][16][17] . Some ectopic ORs also play roles in chemotaxis 18 , muscle regeneration 19 , blood pressure regulation 20 , and hypoxia response 21 .OR51E2, or Prostate Specific G-protein Receptor (PSGR), is one of the most highly conserved and broadly expressed ectopic ORs 22-24 .…”
mentioning
confidence: 99%
“…GPR160 and GPRC5A, two frequently overexpressed GPCRs, are orphan receptors that influence the malignant 12 phenotype. Knockdown of GPR160 in prostate cancer cells increases apoptosis and growth arrest [36]. It has 13 been suggested that GPRC5A is an oncogene that promotes proliferation, migration and colony formation of 14 PDAC cells [11,12].…”
mentioning
confidence: 99%